MINIMIZAÇÃO DOS CUSTOS DE TRANSPORTES RODOVIÁRIO FLORESTAL COM O USO DA PROGRAMAÇÃO LINEAR E OTIMIZAÇÃO DO PROCESSO - Lacowicz, Pedro Giovani; Berger, Ricardo; Timofeiczyk Júnior, Romano; da Silva, João Carlos Garzel Leodoro (Floresta, 2002)
Este trabalho tratou da minimização dos custos do transporte rodoviário florestal, através da programação linear inteira e otimização dos tempos de ciclo de transporte. Após a obtenção dos dados de uma empresa florestal, foram elaborados três cenários, quais sejam: Cenário I: levantamento do quadro atual da empresa, como subsídio comparativo após a racionalização e otimização das etapas que mais consomem tempo do ciclo; Cenário II: realizada em função do uso da programação linear, juntamente com a racionalização dos tempos de fila de espera para carga e descarga; Cenário III: além da programação linear e racionalização dos tempos de espera em fila, utilizou-se, paralelamente, uma otimização do tempo de carga e uma elevação da velocidade de transporte. Os resultados mostraram-se significativos, onde a racionalização e a otimização contribuíram para a redução no número de caminhões e do custo total, traduzindo-se em aumentos na produção dos veículos, na receita bruta e líquida dos freteiros. Cost Minimization of Forest Road Transport by Using the Integer Linear Program and Transport Cycle Time Optimization Abstract This study was about the decreasent of the costs of forest road transport, using the integer linear program and transport cycle time optimization. After obtaining all of the costs, consumed time and the current company picture, a total of three evaluations were done and are described below in settings. Setting I: The current company picture data was calculated as a comparative subsidy following the racionalization and optimization stages that are more time-consuming in the transport cycle. Setting II: This evaluation was done in terms of linear programation use, together with the loading and unloading waiting in line time racionalization. Setting III: In this evaluation, besides the linear programation use and waiting in line time racionalization, it was simultaneously used a time optimization and a foster transport speed. The acquired results were very meaningful, while the racionalization and optimization happened, the trucks rate and total cost successively decreased, resulting in better vehicles performance, and consequently, an increase in the gross and net drivers’ income. Even though there was a costs decrease and an outsiders’ income increase, wich was not enough to pay their total costs, that is, only the variable ones were totally paid and part of the outsiders’ fixed cost.